Letrozole as co-treatment agent in ovarian stimulation antagonist protocol in poor responders: A double-blind randomized clinical trial - Ashraf Moini; Zohreh Lavasani; Ladan Kashani; Maryam Farid Mojtahedi; Nazila Yamini (Shahid Sadoughi University of Medical Sciences, 2019)
Background Ovarian stimulation (OS) for poor ovarian response (POR) patients is still a major challenge in assisted reproductive techniques. Aromatase inhibitors as co-treatment in antagonist protocol are suggested to these patients, but there are controversial reports. Objective To evaluate the effectiveness Letrozole (LZ) as adjuvant treatment in gonadotropin-releasing hormone (GnRH)-antagonist protocol in POR patients undergoing in vitro fertilization/ intracytoplasmic sperm injection cycles. Materials and Methods This double-blind randomized clinical trial was conducted in Arash women's hospital. One hundred sixty infertile women with POR based on Bologna criteria were allocated into two groups randomly: LZ + GnRH-antagonist (LA) and placebo + GnRH-antagonist (PA) groups. In the experimental group, the patients received 5 mg LZ on the first five days of OS with 150 IU of recombinant human follicle-stimulating hormone (rFSH) and 150 IUof human menopausal gonadotropin (HMG). The cycle outcomes were compared between groups. Results The total number of retrieved oocytes and the metaphase II oocytes in LA-treated group were significantly higher than those in the control group (p = 0.008, p = 0.002). The dosage of hMG used and the duration of OS and antagonist administration in LZ-treated group were significantly lower than those of the control group. The number of patients with no oocyte, in the control group, was higher than the LZ-treated group, and the clinical pregnancy rate in LA-treated group (25%) was higher than the control group (18%); however, the differences were not significant statistically. Conclusion Adding 5 mg of LZ to rFSH/hMG antagonist protocol may improve the in vitro fertilization/intracytoplasmic sperm injectioncycle outcome in POR patients.